Consequences of Sensory Modality for Perspective-Taking: Comparing Visual, Olfactory and Gustatory Perception - Kaiser, Elsi (Frontiers in Psychology, 2021)
Perspective-taking is fundamental for language comprehension, including the interpretation of subjective adjectives (e.g. 'fun,' 'tasty,' 'amazing'). To understand these adjectives, one needs to know whose opinion is being conveyed – in other words, who is the attitude-holder or perspectival center. Although the perspective-sensitivity of subjective adjectives has received considerable attention in prior work in formal semantics, potential effects of sensory modality (e.g. sight, taste, smell) on the process of attitude-holder identification have not been systematically investigated. This paper reports a series of studies testing whether interpretation of subjective adjectives depends on whether they refer to the visual, olfactory (smell) vs. gustatory (taste) domains. The results provide evidence that sensory modality has a significant impact on the process of identifying the attitude-holder. This outcome suggests that perspective-sensitivity is highly context-dependent, and the observed modality effects align well with the biological and social properties of sight, taste and smell.